KONTRIBUSI PANJANG LENGAN, KEKUATAN OTOT LENGAN TERHADAP KEMAMPUAN SERVIS ATAS PERMAINAN BOLAVOLY - Hasruddin Hasanuddin (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2018)
This research is a type of descriptive research. The aim of this study; (1) whether there is a contribution to the arm's length, to the ability to serve on the game of volleyball in class XI MAN Kotabaru. (2) whether there is a contribution of arm muscle strength to the ability of the upper service to play volleyball in class XI MAN Kotabaru students (3) whether there is a contribution between arm length and arm muscle strength to the ability of upper service in playing volleyball in class XI MAN Kotabaru students. The population of class VIII students of SMP Negeri 5 Kab Kotabaru, 35 students were sampled. The technique of determining the sample randomly by drawing. Data analysis techniques are descriptive analysis and inferential analysis through SPSS 20.00 program with a significant level of 5% or Î± = 0.05. The results showed that; (1) there is a significant contribution of arm length to the ability to serve up the game volleyball class XI MAN Kotabaru students 37.05%, (2) there is a significant contribution between the strength of the arm muscles to the ability of the upper service in the game bolavoli students of class XI MAN Kotabaru as big as 34.0%, (3) there was a significant contribution jointly between arm length and arm muscle strength to the ability of the upper service to play volleyball in class XI MAN Kotabaru. 53.6%. Keywords: Arm Length, Arm Muscle Strength, upper service.